Antiviral activity of natural and modified hydrocolloids: main sources, susceptible viruses, structure-activity relationship and mechanisms of action - Pereira, Cláudia S. G. P.; Carpena, M.; Barreira, João C. M.; Prieto, M. A.; Oliveira, M. Beatriz P. P. (Frontiers in Nutrition, 2025)
Viruses remain a major global health challenge due to their strict dependence on host cell machinery and limited therapeutic options. Hydrocolloids (natural and semisynthetic) have gained attention as promising scaffolds for antiviral drugs discovery. Their structural variability, biocompatibility, and low toxicity enable diverse mechanisms of action, including inhibition of viral attachment and entry, disruption of replication, immunomodulation, and in some cases direct virucidal effects. This review examines the antiviral activity of hydrocolloids from three main sources: algal (agar, alginate, carrageenan, fucoidan, laminarin, and ulvan); animal (chitin, chitosan, chondroitin sulphate, dermatan sulphate, keratan sulphate, heparin, heparan sulphate, glycogen, and hyaluronan); and plant (pectin derivatives, starch derivatives, and locust bean gum). Across these groups, antiviral efficacy is strongly modulated by structural determinants such as molecular weight, degree and distribution of sulphation, glycosidic linkages, and branching patterns. Sulphated polysaccharides, in particular, exhibit broad-spectrum activity by blocking early infection steps through electrostatic interactions with viral proteins. Despite their potential, challenges persist, including structural heterogeneity, lack of viral specificity, and anticoagulant side effects in certain sulphated derivatives. Strategies to overcome these limitations include chemical modification, development of semisynthetic derivatives, and nanomaterial engineering to enhance stability, bioavailability, and therapeutic precision. Overall, hydrocolloids represent a versatile and underexplored platform for antiviral therapeutics. Continued efforts toward structural optimization, mechanistic elucidation, and clinical translation are critical to unlock their full potential against current and emerging viral threats.